SOUTH AFRICAN MUSIC ENCYCLOPEDIA. Volume II,E to I. Ed. by Jacques P. Malan. Cape Town; Oxford University Press; 1982, pp. 513, illus.. music. - Erlmann, Veit (International Library of African Music, 1983)
pages: 118-120
Keywords: South Africa; African Music